COVID-19 vaccine booster willingness among Asian Americans: Influence of racial discrimination and social determinants - Qiuxi Li; Andrew M. Subica (Human Vaccines & Immunotherapeutics)
Uptake of COVID-19 vaccine booster doses is an important public health topic of study to prevent morbidity and mortality in underserved U.S. populations. However, limited research exists on COVID-19 vaccine booster use and willingness – including its associated factors – among Asian Americans (AA): the fastest growing racial group in the U.S. This study collected survey data from 447 AA adults from three large AA subgroups: Chinese, Korean, and Filipino. Data were collected as part of a community-driven county-wide needs assessment conducted in collaboration with AA community organizations in Riverside County, California. Data indicated that nearly 24% of AA participants received at least four doses of the COVID-19 vaccine, with 36% expressing definite willingness to receive future booster doses. Participants reported experiencing an average of 1.6 instances of racial discrimination across their lifetime. Ordered logistic regression and marginal effects analysis revealed ethnicity, education, racial discrimination, preexisting health conditions, and the number of prior COVID-19 vaccine doses received significantly predicted willingness to receive future vaccine doses. The study suggests that key social factors such as racial discrimination may play an important role in influencing public health efforts to promote vaccine uptake in diverse Asian American populations.